ANALYSIS OF PALM PRODUCTION FACTORS AND BIODIESEL PRODUCTION OPPORTUNITIES IN JAMBI PROVINCE - Irmanelly, Irmanelly; Afrizal, Ardi (Universitas Dharma Wacana, 2025)
Research using secondary data with a quantitative descriptive analysis method which aims to analyze the land area for oil palm commodities in Jambi Province with the finding of an average calculation result of 6.24%. The average number of oil palm commodity farmers is 5.01%. The average price of palm oil commodities is 4.98%. Then for 1 hectare of oil palm the average production amount is 2.03 tons with a production value of IDR 2,732 (million) per month. Then the average land area of oil palm farmers in Jambi Province is 4 hectares with an income of oil palm farmers of IDR 10,290 (million) per month. Then the biodiesel production is 1,644,885 kg on average year